Ex-situ manometric activity test for evaluation of mainstream anammox in Moving Bed Biofilm Reactors. Issue 13 (7th June 2022) - Olsheimer, Dora; la Cour Jansen, Jes; Gustavsson, David J. I.
ABSTRACT: Implementing anammox based processes in the mainstream at municipal wastewater treatment plants is challenging and requires carefully constructed control strategies in order to be successful. A method to measure the specific anammox activity was further developed and implemented in the mainstream anammox pilot plant at Sjölunda Wastewater Treatment Plant. The method was found to be reliable and reproducible. The influence of initial nitrite and ammonium concentrations on the activity as well as temperature dependency were analysed. The continuously monitored manometric batch tests were performed on Moving Bed Biofilm Reactor carriers type K1 ® . The activity showed a dependency of initial nitrite concentrations below 75 mg N L −1 whereas the activity was independent of initial nitrite concentrations in the interval of 75–125 mg N L −1 . Temperature dependency of the specific anammox activity as expressed in activation energy Ea increased at lower temperatures (10–20°C) compared to higher temperatures (20–30°C). Decreasing temperature from 30°C to 10°C resulted in 95–98% loss of the anammox activity. GRAPHICAL ABSTRACT: UF0001